Correlation between defect density and current leakage in InAs∕GaAs quantum dot-in-well structures - Sanchez, A. M.; Beanland, R.; Hasbullah, Nurul Fadzlin; Hopkinson, M.; David, J. P. R. (American Institute of Physics, 2009)
We present a study of InAs/GaAs quantum dot-in-well DWELL material using transmission electron microscopy and leakage current-voltage measurements. The spacer layers between the DWELL layers have a variety of annealing and growth temperatures. We show that there is a strong correlation between spacer layer, annealing temperature, defect density, and these leakage currents, with the most defective sample having 30 times more defects and a leakage current several orders of magnitude above that of the least defective. Cross section transmission electron microscope TEM shows that surface roughness above defective dots is responsible for the high defect densities. However, even in the best sample the reverse bias leakage current is several orders of magnitude above that typically seen in quantum well materials and a measurable density of defective dots are observed in planar view TEM. © 2009 American Institute of Physics